Development and validation of ARSAC-CORTH coupling code based on a generic coupling architecture - Wang, Xiaoyu; Qiu, Zhifang; Peng, Shinian; Deng, Jian; Zeng, Wei; Liu, Luguo; Zhang, Xilin; Zhang, Xue; Xia, Yunfeng; Wang, Mingjun (Frontiers in Energy Research, 2024)
Reactor thermal-hydraulic codes can be categorized into system codes, sub-channel codes and CFD (computational fluid dynamics) codes according to the spatial discretization and simplification methods. As a traditional reactor system safety analysis code, system code is able to analyze the overall performance of the reactor quickly, while it cannot capture the mixing effects between coolant channels in the core accurately. The sub-channel code is currently the most suitable code for core analysis, with higher fidelity than system code and less computation resources than CFD code. To perform analysis of coupling effects between thermal-hydraulics characteristics of the reactor system and those of core, the in-house system code ASRAC and the in-house sub-channel code CORTH are coupled based on a generic coupling architecture. This generic coupling architecture comprises the generic coupling interface concept ICoCo (Interface for Code Coupling) and the generic data exchange model MED (Model for Exchanging field Data). In order to evaluate the accuracy and capability of the coupling code, the LOFT experiment case is chosen and analyzed. According to the validation results, compared with ASRAC code standalone, the ARSAC-CORTH coupling code is able to better analyze the coupling effects of loop system and core, meanwhile capturing the coolant mixing between coolant channels.